Policy Level Improvement in Hydropower Development - Thapa, Bikash Thapa (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Mother Nature has given Nepal a vast opportunity for hydro energy production, but still the country is reeling under painful load shedding due to an electric power production deficit of 70MW. The main challenge for the country now is to harness the hydropower potentiality, which contributes for its economic development. In Nepal, policy deficiencies and the slow decision making process in electricity sector has resulted in the increased project costs and has reduced the involvement of private sectors and the entrepreneurs. Thus, restructuring and improvements at all policy level is required to overcome various hurdles, and then only will hydropower develop in Nepal. Hydro Nepal: Journal of Water, Energy and Environment Vol. 1, No. 2(2008) pp. 17-18